2013
DOI: 10.1088/1742-6596/434/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria for mass lesions differentiating in electrical impedance mammography

Abstract: Abstract. The purpose of this research was to determine the diagnostic criteria for differentiating volu metric lesions in the mammary g land in electrical impedance mammography. The research was carried out utilizing the electrical impedance computer mammograph «MEIK v.5.6» ® , which enables to acquire images of 3-D conductivity distribution layers within mamma's tissues up to 5 cm depth . The weighted reciprocal projection method was emp loyed to reconstruct the 3-D electric conductivity distribution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Optimization of RF thermal ablation depends upon the availability of detailed and accurate electrical properties of tissues, and these properties can also be of use in detection of the tumor for diagnostics purposes. In fact, knowledge of tissue electrical properties has been used to distinguish between normal tissue and tumor tissue for breast cancer and cervical carcinomas (Kerner et al 2002, Miranda et al 2012, Karpov et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of RF thermal ablation depends upon the availability of detailed and accurate electrical properties of tissues, and these properties can also be of use in detection of the tumor for diagnostics purposes. In fact, knowledge of tissue electrical properties has been used to distinguish between normal tissue and tumor tissue for breast cancer and cervical carcinomas (Kerner et al 2002, Miranda et al 2012, Karpov et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The results of 3D EIT imaging were analyzed independently based on visual interpretation and quantitative evaluation of breast tissues and according to the main diagnostic criteria previously reported from Russia (13)(14)(15). The breast's structure, contour, focal changes of electrical conductivity, and bilateral breast conductivity differences were evaluated to analyze the possibility of pathological changes in the patient's breast.…”
Section: Image Analysismentioning
confidence: 99%
“…Furthermore, many reports over the past century have shown that the electrical properties of tumor-bearing tissue differ from normal tissue with sufficient contrast for distinguishing tissue heterogeneities in animal and human tissue (Fricke and Morse 1926, Haemmerich et al 2003, 2009, Laufer et al 2010, Prakash et al 2015. In fact, tissue electrical properties have been used to distinguish between normal tissue and tumor tissue for breast cancer and cervical carcinomas (Kerner et al 2002, Miranda et al 2012, Karpov and Korotkova 2013, Ma and Soleimani 2020 with an expanded data set recently reported for evaluating properties of CRC tissues at different tumor stages (Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%